Iowa Birdline update, January 9, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for January 9, 1989. Highlights include sightings of a Barrow's Goldeneye, a Varied Thrush and an Ovenbird. Epson - sheet feed/flatbed